CHARGING STATIONS CONNECTED TO STREET LIGHT POWER SYSTEMS - Peter Janiga (Journal of Energy Technology, 2025)
Street light grids are dense and compact networks in all cities. They power the luminaires and elements of smart cities. Recently, they have also been used to power chargers for electric vehicles. The article analyses how charging stations can be connected to public lighting networks, and gives knowledge about connecting the charger and optimising operations to increase the power delivered to vehicles. Initial installations show that the combination of luminaires, public lighting networks and chargers shows specific characteristics. The aim of the paper is to provide knowledge about the implementation of chargers in street light grids. The last part of the paper presents the results a case study, which is focused on voltage drops and limits for installing charging stations.